Regulatory Dynamics And Worker Rights Protection: An Evaluation Of Labor Law And Job Creation In Indonesia - Dharma Setiawan Negara; Agung Satryo Wibowo; Didit Darmawan; Budi Santoso; Nanang Saputro Agung Widodo (Jurnal Hukum Lex Generalis, 2024)
The reform of labor law in Indonesia, particularly through the Job Creation Law, aims to adapt labor policies to the demands of the global market and strengthen the national economy. This study evaluates the effectiveness of Law Number 13 of 2003 on Manpower and the changes brought by the Job Creation Law, focusing on the protection of workers' rights and its effect on social justice. The analysis shows that while the new law offers greater flexibility in employment contracts and working period arrangements, there is a significant risk of a reduction in worker protection standards. The study underscores the urgent need for more effective oversight mechanisms and policy advice to ensure that the legal changes contribute positively to workers' lives without compromising their rights.